Association of lung-intestinal microecology and lung cancer therapy - Kong, Ling-Yu; Chen, Xuan-Yu; Lu, Xin; Caiyin, Qinggele; Yang, Dong-Hua (Chinese medicine, 2023)
In recent years, the incidence of lung cancer is increasing. Lung cancer has become one of the most malignant tumors with the highest incidence in the world, which seriously affects people’s health. The most important cause of death of lung cancer is metastasis. Therefore, it is crucial to understand the mechanism of lung cancer progression and metastasis. This review article discusses the physiological functions, pathological states and disorders of the lung and intestine based on the concepts of traditional Chinese medicine (TCM), and analyzes the etiology and mechanisms of lung cancer formation from the perspective of TCM. From the theory of “the exterior and interior of the lung and gastrointestinal tract”, the theory of “the lung-intestinal axis” and the progression and metastasis of lung cancer, we proposed e “lung-gut co-treatment” therapy for lung cancer. This study provides ideas for studying the mechanism of lung cancer and the comprehensive alternative treatment for lung cancer patients.